Combination technique by using immunostimulant and drugs in artificial feeds for bacterial eradication in Seabass - Manja Meyky Bond (Jurnal Perikanan dan Kelautan, 2011)
Pathogenic bacterial namely Streptococcus sp has widely spreads in Seabass culture, particularly in fingerlings. It might caused decreasing production quality and quantity. To improve this problem, a study have been done to feed the seabass by using the combination of immunostimulan and antibiotics. The parameter observed were the survival rate and growth rate. Juveniles of 2 cm in size with Streptococcus symptoms were reared in 6 units of 2 m3 tanks with stocking density of 5,000 fishes per tank. They were fed with artificial feeds mixed by immune stimulant and antibiotics (5gr/kg and 2gr/kg, respectively). The experiment was done with 3 replicates and one control for 20 days. The results showed that the survival rates were significantly different between A and B (control) with 20.2% (3,030 ind) and 12.5% (1,875 ind), respectively. There were no significant different in the growth rates between A and B with body length 5.90 cm and 5.80 cm, respectively.